Bay of Bengal maritime delimitation cases: Upholding the Rule of law in international relations. (2nd January 2018) - Rajput, Aniruddha
ABSTRACT: At a time when there are instances of lack of participation in binding dispute resolution mechanisms under the UNCLOS, the Bay of Bengal Arbitrations provide a ray of hope and adherence to the rule of law. The three Bay of Bengal States: Bangladesh, India and Myanmar settled their long standing disputed claims over the maritime zones in the Bay of Bengal in a peaceful manner. These cases represent that States relatively stronger on the political level as compared to others are willing to compromise their positions and adhere to the outcome of dispute resolution proceedings under the UNCLOS. These cases involved sensitive issues such as the determination of the land boundary terminus, based upon the reports and other proceedings relating to the partition of India. There were other controversial claims over certain islands, which too were presented for adjudication and the decision was thereafter complied with all the parties to the dispute. These cases thus constitute a prime example of the importance of adherence to a rule based system for maritime claims.